2020
DOI: 10.1016/j.celrep.2020.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Vagal Cocaine- and Amphetamine-Regulated Transcript Promotes Hyperphagia and Weight Gain

Abstract: Highlights d CART is a molecular signal that encodes caloric information for meal termination d Vagal CART synthesis is blunted in obesity partly due to reduced sensitivity to CCK d Knockdown of vagal sensory CART increases food intake by preventing negative feedback d NTS administration of CART inhibits food intake in both lean and obese rats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
0
23
0
1
Order By: Relevance
“…The meal patterns changes in rats were restricted to the dark phase irrespective of diet, presumably because rodents consume the majority of their food in the dark. Interestingly, other feeding studies in which vagal sensory signalling was impaired also reported disruption of meal patterns only in the dark, 49,50,70 and is therefore a conserved phenomenon. In HFHS‐fed animals, vagal gut‐brain signalling conveys signals that affect both satiation and satiety, resulting in pronounced hyperphagia.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The meal patterns changes in rats were restricted to the dark phase irrespective of diet, presumably because rodents consume the majority of their food in the dark. Interestingly, other feeding studies in which vagal sensory signalling was impaired also reported disruption of meal patterns only in the dark, 49,50,70 and is therefore a conserved phenomenon. In HFHS‐fed animals, vagal gut‐brain signalling conveys signals that affect both satiation and satiety, resulting in pronounced hyperphagia.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, post‐prandial neuronal activation in the NTS is significantly lower in obese, compared to lean, rats, 47,91 suggesting that gut‐brain signalling is severely blunted. Our previous work demonstrates that disrupted vagal signalling coincides with the onset of hyperphagia 44,50 . The exact mechanism by which vagal signalling is reduced in obesity remains unclear but may involve blunted receptor expression, 44,92‐95 impaired neuropeptide release 50 and/or altered biophysical properties 37 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The anorectic effect of CCK is impaired in HFD-fed mice and rats 55 , as is vagal afferent activation 55 , although this has not been fully examined in humans. Further, CCK-1R expression in vagal nerves is decreased in HFD induced obese rats 56 , ultimately contributing to reduced nodose ganglia cocaine and amphetamine-regulated transcript (CART) expression, a neuropeptide regulating energy homeostasis, in association with increased food intake and body weight 64 . However, vagal CCK resistance during obesity could also be due to obesity-associated leptin resistance, as the leptin receptor is co-expressed with CCK-1R in the vagal afferent neurons 65 and leptin potentiates the suppressive effect of CCK on appetite and increases vagal afferent activation following CCK administration 66 , 67 .…”
Section: Gi Nutrient-sensing Physiologymentioning
confidence: 99%